Answer:
[tex]g'_h=1.096\times 10^{-5}\ m.s^{-2}[/tex]
Explanation:
We know that the gravity on the surface of the moon is,
Gravity at a height h above the surface of the moon will be given as:
[tex]g'_h=\frac{G.m}{(r+h)^2}[/tex] ..........................(1)
where:
G = universal gravitational constant
m = mass of the moon
r = radius of moon
We have:
Now put the respective values in eq. (1)
[tex]g'_h=\frac{6.67\times 10^{-11}\times 7.35\times 10^{22}}{(1.74\times 10^6+384.4\times 10^6)^2}[/tex]
[tex]g'_h=1.096\times 10^{-5}\ m.s^{-2}[/tex] is the gravity on the moon the earth-surface.